Soybean performance in grouped and conventional sowing with pneumatic seeder at different operational speeds - Lopes, Arthur Gabriel Caldas [UNESP]; da Silva Correia, Tiago Pereira; Taveira, Wesley Matheus Cordeiro Fulgêncio [UNESP]; Pereira, Gabriela Greice; de Souza, Alyne Ayla Rodrigues (Revista de Agricultura Neotropical, 2021)
Conventionally, soybean sowing is carried out by distributing the seeds individually and equidistantly along the sowing furrow. An alternative is the grouped dosage and distribution of seeds, just rearranging them. The aim of this work was to evaluate the agronomic characteristics of soybean sown with a grouped and conventional seed metering disc in a pneumatic seeder at different operating speeds. The experimental design adopted was completely randomized (CRD) under a 2 x 3 factorial scheme, with two spatial sowing arrangements, grouped and conventional, and three sowing speeds, 4.5; 5.2 e 6 km h-1, resulting in six treatments with four repetitions each. The results show a productive increase between 20.7% and 39.9% for the grouped arrangement at speeds of 5.2 and 4.5 km h-1, respectively. The higher sowing speed, limits the grouping of seeds to the grouped arrangement.
Desempenho de soja em plantio agrupado e convencional com dosadores pneumáticos
Keywords: Agronomic characteristics; Glycine max; Spatial arrangement